1998
DOI: 10.1016/s0022-5347(01)63709-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum Interleukin-6 Levels in Metastatic Renal Cell Carcinoma Before Treatment With Interleukin-2 Correlates With Paraneoplastic Syndromes but Not Patient Survival

Abstract: IL-6 was frequently secreted by renal cancer cell lines but it was only present in the serum of approximately half of the patients with metastatic renal cancer. Elevations of serum IL-6 were associated with paraneoplastic manifestations frequently seen in patients with renal cancer, including anemia, thrombocytosis, decreased albumin and elevations of alkaline phosphatase (Stauffer's syndrome). A weak relationship was noted between serum IL-6 level and fever but none was noted between that and survival or resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…IL-6 expression, meanwhile, was 19.88-fold upregulated in the Caki-1 cell line. mRCC (40,74). STATs are a family of cytoplasmic proteins that take part in transcription of genes involved in diverse cellular activities in disease states (8,44), and the expression of STAT1, STAT2, STAT4, and STAT6 genes was observed to be elevated (4.86, 4.25, 3.48, and 3.03, respectively) in Caki-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 expression, meanwhile, was 19.88-fold upregulated in the Caki-1 cell line. mRCC (40,74). STATs are a family of cytoplasmic proteins that take part in transcription of genes involved in diverse cellular activities in disease states (8,44), and the expression of STAT1, STAT2, STAT4, and STAT6 genes was observed to be elevated (4.86, 4.25, 3.48, and 3.03, respectively) in Caki-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In samples with a positive MSP band, the relative methylation ratio was determined after the MSP or USP product was electrophoresed in nondenaturing 12% polyacrylamide gels. The area under the curve (AUC) corresponding to each band was calculated using ImageJ software, 4 and the relative methylation level was determined [MSP ratio = MSP band density / (MSP band density + USP band density)] as reported previously (17,18).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, f10% of patients with locally confined tumors die of disease progression within 5 years of nephrectomy (3). Although several prognostic variables for RCC, such as serum interleukin-6 or immunosuppressive acid protein, have been proposed, they have not been shown to be reliable tumor markers due to low specificity and sensitivity (4,5). Therefore, accurate preoperative prognostic biomarkers are needed to distinguish highly malignant RCCs to aggressively treat them or put them under stringent surveillance.…”
mentioning
confidence: 99%
“…Previous large scale studies on IL-2 treatment have shown that pretreatment high inflammatory activation, measured by markers such as IL-6 and CRP, predicts lack of IL-2 activity on tumour objective response and its efficacy on overall survival in metastatic cancer patients (Blay et al, 1992;Tartour et al, 1994). However, a separate, smaller study demonstrated that detectable IL-6 serum levels correlated with paraneoplastic syndromes but not with response or survival (Walther et al, 1998). Regarding lymphocyte count changes, some studies (Palmer et al, 1993;Gohring et al, 1996) demonstrated that a greater lymphocyte increase after s.c. IL-2 administration occurrs in metastatic renal cell cancer patients with objective response.…”
Section: Discussionmentioning
confidence: 99%